DEVELOPMENT OF E-BOOK USING BOOK CREATOR TO ENHANCE STUDENTS UNDERSTANDING OF NARRATIVE TEXT ON READING SKILL - Muhammad Farras Fadhil; Siti Niah; Prih Febtiningsih (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
This research aims to develop a digital learning medium in the form of an interactive e-book using Book Creator to enhance students’ understanding of narrative texts in English reading skills. The study was conducted at SMP Tuah Negeri Pekanbaru and employed the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The e-book was designed based on curriculum indicators and equipped with multimedia features such as audio narration, videos, illustrations, and interactive quizzes to support student engagement and comprehension. Validation was conducted by content and media experts, yielding a feasibility score of 92%, categorized as